Pengaruh CR, DAR, dan ITO terhadap NPM pada PT Indocement Tunggal Prakarsa TBK Periode 2014-2023 - Taufiqurrahman; Priyanto, Aria Aji (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The current ratio, debt-to-asset ratio, inventory turnover-to-net profit margin, and other financial ratios of PT Indocement Tunggal Prakarsa Tbk will be partially and concurrently studied from 2014 to 2023. Data used in associative quantitative study comes from PT Indocement Tunggal Prakarsa Tbk's financial report, which comprises secondary sources. Testing hypotheses, doing regression analysis, and calculating coefficients of determination are all examples of traditional data analysis approaches. This research's findings indicate a positive and statistically significant correlation between the Current Ratio and Net Profit Margin, as shown by a computed t value of 12.045 > t table 2.447 and a significance level of 0.000 < = 0.05. The debt to assets ratio positively impacts net profit margin, according to the findings of the hypothesis testing (tcount 7.493 < ttable 2.447, p-value < 0.05). Results from the hypothesis test indicate that inventory turnover does not significantly impact net profit margin (tcount -3.759 < 2.447, significance value 0.009 < 0.05). Results show that the current ratio, debt to assets ratio, and inventory turnover significantly impact net profit margin (p 0.000, p < 0.05, and Fcount 75.981 > Ftable 4.35). Our three current ratios—debt to assets, inventory turnover, and current ratio—explain net profit margin with a coefficient of determination of 96.2%.